Download presentation
Presentation is loading. Please wait.
Published byViktor Rosenberg Modified over 6 years ago
1
Function Notation “f of x” Input = x Output = f(x) = y
2
(x, y) (x, f(x)) (input, output) y = – 3x+6 f(x) = – 3x+6 x y x f(x)
Before… Now… y = – 3x+6 f(x) = – 3x+6 x y x f(x) -2 -1 1 2 12 -2 -1 1 2 12 (x, y) (x, f(x)) 9 9 6 6 3 3 (input, output)
3
g(2) = 2 3 g(5) = Find g(2) and g(5).
Example Find g(2) and g(5). g = {(1, 4),(2,3),(3,2),(4,-8),(5,2)} g(2) = 2 3 g(5) =
4
Consider the function h= { (-4, 0), (9,1), (-3, -2), (6,6), (0, -2)}
Example Consider the function h= { (-4, 0), (9,1), (-3, -2), (6,6), (0, -2)} Find h(9), h(6), and h(0).
5
Example. f(x) = 2x2 – 3 Find f(0), f(-3).
6
Example. f(x) = 3x2 +1 Find f(0), f(-1).
7
What are your questions?
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.